2016
DOI: 10.1002/rev3.3077
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of metacognition in children aged 4–16 years: a systematic review

Abstract: This article presents the results of a systematic review of methods that have been used to measure or assess metacognition in children aged 4–16 years over a 20‐year period (1992–2012). It includes an overview of the types of tool and methods used linked with the ages of the participants targeted and how metacognition and associated concepts are defined. Two thousand, seven hundred and twenty‐one records were identified through systematic searching; 525 articles or reports were full text screened, resulting in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 203 publications
1
54
0
Order By: Relevance
“…We found that Laura tended to provide relatively superficial responses to prompts—prompts that were themselves relatively broad and procedural. More widely, this finding highlights the close association between the tools of measurement of metacognition and the way that metacognition is judged resultantly (Desoete, ; Gascoine et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…We found that Laura tended to provide relatively superficial responses to prompts—prompts that were themselves relatively broad and procedural. More widely, this finding highlights the close association between the tools of measurement of metacognition and the way that metacognition is judged resultantly (Desoete, ; Gascoine et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Amy may not have been able to express herself in writing, and may not have developed the language of thinking and learning required to express herself in the ways that these STAs demand. More broadly, this finding again highlights that the evidence of metacognition is ultimately bound within the tool of measurement (Gascoine et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…As we have argued, observations are a meaningful, nondisruptive way to identify metacognitive behaviors, yet few observation protocols exist for older students. For example, a systematic review of metacognition assessment tools for children aged 4–16 years found that observational protocols (without think‐aloud prompting) have not been used with students older than 9 years of age (Gascoine, Higgins, & Wall, ). We did not find a similar systematic review for older students, but our general literature searches have had scant results regarding observational protocols.…”
Section: Discussionmentioning
confidence: 99%